Euroscepticism: The rise and fall of Euroscepticism in Iceland and the United Kingdom - Róbert Ingi Ragnarsson 1996- (2021)
Iceland has seen a rise in Euroscepticism since the BREXIT vote while The United Kingdom has seen a decline in Euroscepticism. These two states vary greatly historically, politically, culturally and in size, but they do have a common history of Euroscepticism and a reluctance towards European integration. The United Kingdom has recently completed the process of leaving the European Union while Iceland is still debating whether or not to apply for membership. Using both classical definitions of Euroscepticism (Hard and soft Euroscepticism) and a more nuanced definition (discursive Euroscepticism) this thesis explores the history of Euroscepticism in each state and the reasons for it in order to explain the change in the attitude towards European integration in those states. It also explores two crises that the European Union has faced; The financial crisis which has passed but should be used in order to learn from the mistakes the EU made during the crisis and the ongoing legitimacy crisis with the complication of the democratic deficit. The essay also focuses on the newly popularized “fake news” topic and how misinformation can fuel Euroscepticism. The essay finds that the main cause for the rise in Euroscepticism is the strong ties the fishing industry has towards the parliament and the unequal number of MPs favouring the rural area which is more reliant on agriculture and the fishing industry. It also finds that misinformation can be used as a tool to further enhance Euroscepticism because the EU faces a legitimacy crisis that is easily abused by Eurosceptics to fuel Eurosceptic mindsets. The thesis also finds that the main reason for the decline in Euroscepticism in the United Kingdom may be due to misinformation as well, i.e. the fact that all the promises made by those who were endorsing the United Kingdom to leave the EU turned out to be false. (Most notably the infamous bus that promised 350 million pounds that could be spent on the NHS). The decline is partly because the UK made a poor deal with the EU ...